The Pentagram as a Medical Symbol : An Iconological Study - Schouten, Jan (European History and Culture - Book Archive pre-2000., 1968)
The five-pointed star drawn in an unbroken line is the subject of the present study. During the 16th century until into the 17th century the pentagram was a well-known medical emblem; nowadays it is almost completely forgotten.